Development and Validation of a Questionnaire to Assess Role Conflicts Among Interpreters Working With Refugee Clients: The Role Conflicts Questionnaire - Angelika Geiling; Angelika Geiling; Laura Nohr; Caroline Meyer; Maria Böttche; Maria Böttche; Christine Knaevelsrud; Nadine Stammel (Frontiers Media S.A., 2023)
Objectives: The aim of this study was to develop and validate a questionnaire to assess interpreters' role conflicts and the challenging aspects within the triad of practitioner, interpreter and refugee client.Methods: A questionnaire was developed based on previous literature. Its factor structure and construct validity were assessed in an online survey of 164 interpreters working with refugee clients. Psychological distress (BSI-18), work-related exhaustion (CBI), and secondary traumatic stress (ProQOL) were measured to test the questionnaire's convergent validity.Results: Exploratory structural equation modeling for categorical variables resulted in 23 items across four subscales. The scores of all subscales had good or excellent reliability (ω = 0.81 to ω = 0.93) and correlation analyses indicated convergent validity.Conclusion: The final questionnaire (RoCo) showed four clearly interpretable subscales and may help to identify emotional distress due to role conflicts among interpreters. Future studies should validate the questionnaire in different samples.